An Act for Establishing a Militia in this Government (1756) - (:unkn) unknown (My University, 1756)
Prohibited meeting of the militia within a half mile of a inn or tavern, and prohibited the sale of strong liquor within a half mile of the state militia.
Keywords: MILITIAS